2023
DOI: 10.1097/js9.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous resection of colorectal cancer and synchronous liver metastases: what determines the risk of unfavorable outcomes? An international multicenter retrospective cohort study

Abstract: Background: The use of a simultaneous resection (SIMR) in patients with synchronous colorectal liver metastases (sCRLM) has increased over the past decades. However, it remains unclear when a SIMR is beneficial and when it should be avoided. The aim of this retrospective cohort study was therefore to compare the outcomes of a SIMR for sCRLM in different settings, and to assess which factors are independently associated with unfavorable outcomes. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Sijberden et al reported a retrospective study from an international database with 766 patients with synchronous CRCLM submitted to different types of liver and colorectal resection. They concluded that synchronous resection should be reserved for CRCLM patients in whom minor liver resection would suffice and those requiring a left-sided colectomy [145].…”
Section: Crclm-best Surgical Algorithm Approachmentioning
confidence: 99%
“…Sijberden et al reported a retrospective study from an international database with 766 patients with synchronous CRCLM submitted to different types of liver and colorectal resection. They concluded that synchronous resection should be reserved for CRCLM patients in whom minor liver resection would suffice and those requiring a left-sided colectomy [145].…”
Section: Crclm-best Surgical Algorithm Approachmentioning
confidence: 99%